Imagens da escola: a informática educativa no Colégio Pedro II - Costa, Sandra Silva (2010)
This dissertation aims to answer a specific question: how does an area, like Educational Informatics, that proposes a new school culture develop and manage to establish itself as a particular area in a secular school with strong humanistic tradition? The ideas and writings of the Chilean researcher, philosopher and scholar José Joaquin Brunner, oriented us during our research and reflections on the contemporary social transformation that has resulted from the approximation of two fields of knowledge, Education and the new technologies developed in the field of Information and Communication. During our investigation we decided to use audiovisual instruments and resources to register, in different spaces and times of the school chosen for observation – Colégio Pedro II –, the relevant characters and the insertion of cultural practices based on the Information and Communication technologies. We also decided to present as part of this research the 26-minute documentary film we have shot based on the people’s testimonials that have directly and indirectly taken part in the implantation of this new area in Colégio Pedro II School. Our film is called Imagens da Escola: A Informática Educativa no Colégio Pedro II (Images of the School: Educational Informatics at Colégio Pedro II) and is composed of three blocks: Primeiros Movimentos (First Movements), Espaços e Bandeiras (Spaces and Flags) and Informática Educativa, espaço em construção (Educational Informatics, space in construction).